2018
DOI: 10.1002/ags3.12220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the modified Collard and hand‐sewn anastomosis for cervical esophagogastric anastomosis after esophagectomy in esophageal cancer patients: A propensity score‐matched analysis

Abstract: BackgroundSeveral studies have reported that modified Collard anastomosis is useful for cervical anastomosis after esophagectomy for thoracic esophageal cancer. However, no large‐scale study has confirmed the efficacy of the modified Collard anastomosis.MethodsBetween 2008 and 2016, 398 consecutive esophageal cancer patients who underwent esophagectomy and cervical anastomosis were enrolled in this study. Patients with a short remnant cervical esophagus were excluded. We investigated the utility of the modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
0
30
1
Order By: Relevance
“…According to the study by Prince et al the rate of anastomotic stricture after MC was 24%, 21 and according to another study reported by Ercan et al the incidence of anastomotic stricture was 66%. 20 Sugimura et al showed that MC yielded a rate of stricture of 22%, 9 whereas the study by Behzadi et al revealed that the rate of stricture after modified Collard anastomosis was 4.6%, 22 which was lower compared with that in our study (18.8%). The insertion length of the staple in the anastomosis of the posterior wall could be the potential reason for this difference.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…According to the study by Prince et al the rate of anastomotic stricture after MC was 24%, 21 and according to another study reported by Ercan et al the incidence of anastomotic stricture was 66%. 20 Sugimura et al showed that MC yielded a rate of stricture of 22%, 9 whereas the study by Behzadi et al revealed that the rate of stricture after modified Collard anastomosis was 4.6%, 22 which was lower compared with that in our study (18.8%). The insertion length of the staple in the anastomosis of the posterior wall could be the potential reason for this difference.…”
Section: Discussioncontrasting
confidence: 85%
“…One of the superiorities of the modified Collard anastomosis is its large anastomotic diameter. The study of Behzadi et al 22 reported an insertion length of 45-50 mm resulting in a low stenosis rate and Sugimura et al 9 reported a 40 mm insertion length of the staple in the anastomosis. The insertion length in our study was 45 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increase in the diameter of the anastomosis, the probability of re ux did not increase in the patients of their study (31). Sugimura and colleagues showed that frequency of re ux esophagitis tended to be lower in the mechanical group than in the hand-sewn group prior to propensity score matching (26). In our study, the length of the remaining cervical esophagus was longer than the hand-sewn group in order to create a proper anastomosis in the stapled group.…”
Section: Sugimura Et Al Used a Modi Edmentioning
confidence: 58%
“…The authors showed that anastomotic leakage was less frequent in the modi ed Collard group than in the hand-sewn group but that the difference was not signi cant. Anastomotic stenosis occurred to a signi cantly lower extent in the modi ed Collard group, and the period between esophagectomy and initial dilatation was signi cantly shorter in the hand-sewn anastomosis group (26). Similarly, Ishibashi et al performed triple-stapled quadrilateral anastomosis to create esophagogastric anastomosis and reported no signi cant anastomotic leakage and stricture (27).…”
Section: Sugimura Et Al Used a Modi Edmentioning
confidence: 98%